Humanity-Based Language Learning - Rosida Tiurma Manurung; Evany Victoriana; Alfredo Ezra Amadeus (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
This research is about language learning with a human perspective. The purpose of this paper is to find out how students respond and respond to language learning with a humanitarian perspective among active students. This research is a research with a qualitative descriptive analysis approach, namely a technique that analyzes, describes, and summarizes various situations and conditions. The data collection technique in this study was using a questionnaire aimed at active students with ages between 18-25 years, in the questionnaire presented statements that needed to be answered by respondents in a factual and honest manner. Based on the results of research on language learning with a humanitarian perspective, it was found that the majority of respondents used good and correct Indonesian with human values because it grew from an attitude of caring for others and an attitude of helping. This study also found that students have respected the state language as a language of instruction in the world of education, students agree that human values can be developed to shape one's character so that it can be implemented in language learning and there is concern with Indonesian language education for the wider community with values. human values.